Consistent red luminescence in π-conjugated polymers with tuneable elastic moduli over five orders of magnitude. Issue 5 (11th March 2020) - Guo, Zhenfeng; Shinohara, Akira; Pan, Chengjun; Stadler, Florian J.; Liu, Zhonghua; Yan, Zhi-Chao; Zhao, Jinlai; Wang, Lei; Nakanishi, Takashi
Abstract : Bulky but flexible alkyl side chains enable π-conjugated polymers to possess wide-range elastic modulus tuneability, yet consistent red luminescent properties. Abstract : Here, we present a rational strategy for a wide-range of predictable tuning methods for the elastic modulus ( G ′) of alkylated π-conjugated polymers (Alk-CPs). Alk-CPs and their blends exhibit consistent emission chromaticities despite a drastic change in G ′, which would help in the straightforward design of future optoelectronically active soft materials.